Pigmentary Disorders; Vitiligo and Melasma in Context of South Asian Countries: A Psychosocio-Cosmetic Challenge - Anil K Jha; Subekcha Karki (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2015)
Vitiligo and melasma are acquired pigmentary disorder of the skin and also the leading cause for dermatologist consultation in South Asian countries like Nepal. Vitiligo vulgaris and melasma are common examples for depigmentary and hyperpigmentary conditions respectively. There are multiple proven medical, surgical and combined modalities of managing them but the challenge in our part of the world with majority of Fitzpatrick skin types III-V is; it remains a psychosocial-cosmetic disease.